Performance scaling of ultrafast two micron fiber CPA systems and high-power nonlinear pulse compression to the sub-2 cycle regime - Gebhardt, Martin; Gaida, Christian; Heuermann, Tobias; Wang, Ziyao; Jauregui, Cesar; Antonio-Lopez, Jose; Schülzgen, Axel; Amezcua-Correa, Rodrigo; Rothhardt, Jan; Limpert, Jens (Proceedings of SPIE - The International Society for Optical Engineering, 2019)
High repetition rate sources of energetic, few-cycle pulses are useful tools for strong-field science and high-harmonic generation (HHG). Concerning HHG, a carrier wavelength beyond the well-explored near infrared spectral region is very attractive for increasing the phase-matched photon-energy cut-off. In particular, driving laser wavelengths spanning 1-2 µm make it possible to access the highly application relevant spectral region between 300 eV and 500 eV. In this contribution, we report on the current status and on the future prospects of ultrafast thulium-doped fiber laser systems operating around 1.9 µm wavelength. Average power scaling to 1 kW and peak power scaling to several GW is presented, together with the demonstration of 100 fs pulses emitted directly from a high energy fiber laser. Using a gas-filled, antiresonant hollow-core fiber, nonlinear self-compression of the pulses from a thulium-doped fiber CPA is investigated at 392 kHz repetition rate. We have achieved a record average power of 44 W, 5 GW of peak power and sub-two cycle pulse duration with a spectrum spanning 1.0-2.2 µm. Based on these results, we discuss future performance scaling and applications of the laser source.
CRIS-Team Scopus Importer:2023-04-20
Keywords: Fiber laser; Nonlinear pulse compression; Nonlinear spectral broadening